Port site infection by Mycobacterium fortuitum after laparoscopic hysterectomy and its management– A case report - Farook, Abdulrazack; Kannan, Iyanar; Gunasekaran, N; Premalatha, E; Dineshraj, R (Asian Journal of Medical Sciences, 2021)
In the department of gynaecology vaginal hysterectomy and laparoscopic hysterectomy are popular methods of surgery. They involve less amount of blood loss, with short hospital stay. In recent times, laparoscopic hysterectomy is done commonly. Forty-two-year female was admitted in surgery ward, Tagore Medical College and Hospital, with pain in abdomen at the laparoscopic site and lower abdomen. Pus discharge through the port site, left loin for the last 3 months. The microbiological examination of the pus showed the presence of Mycobacterium fortuitum. After identification of atypical mycobacterium, the patient was administrated with amikacin injection for 3 months and clarithromycin and ofloxacin tablet for one year. Patient was discharged and was advised to come for periodical review.